Utilization of radioguided occult lesion localization (ROLL) method in thyroid and parathyroid surgery - Jankulovska, A; Stojanoski, Sinisha; Manevska, Nevena; Makazlieva, Tanja; Majstorov, Venjamin; Miladinova, Daniela (Springer Science and Business Media LLC, 2021)
Aim/Introduction: Assessment of the feasibility and effectiveness of radioguided occult lesion localization (ROLL) technique in patients undergoing surgical intervention for excision of hyperfunctional parathyroid tissue and remnant thyroid tissue or lymph node (LN) dissection in patients with confirmed thyroid carcinoma (TC). Materials and Methods: The study group consisted of 18 patients undergoing ROLL from January 2017 to December 2018. 11 patients (54±13,91 years, five females and six males) were diagnosed with primary hyperparathyroidism (confirmed by laboratory tests for PTH, calcium and phosphorus levels and parathyroid ultrasound performed before surgery). All underwent dual phase 99m Tc-MIBI parathyroid SPECT/CT scintigraphy for correct preoperative parathyroid adenoma localization. Another 7 patients (52,83±11,68 years, five females and two males) with histologically proven thyroid carcinoma were scheduled for reoperation (5 patients due to papillary TC remnant tissue, 1 patient due to recurrent papillary TC and 1 patient due to LN metastasis of medullary TC). Ultrasound guided injection of 7 Mbq 99m Tc-macroagregate in each lesion on the day of the surgery had been applied. Subsequently ROLL technique with gamma probe had been used intraoperatively to correctly identify the tissue for excision. Results: Parathyroid adenomas were confirmed histologically in all 11 patients. Mean PTH and total calcium levels were measured prior to parathyroid surgery and were 1599,21±912,59 pg/ml and 2,89±0,67 mmol/L, respectively. Parathyroid adenoma’s size ranged from 8 to 21 mm. In patients operated due to the remnant thyroid tissue, lesions ranged from 21 to 27 mm in diameter, measured postoperatively. In 1 patient who underwent excision of recurrent papillary TC total of 3 foci were excised, ranging 7-17 mm in diameter. Lymph node dissection was performed in 1 patient with medullary TC and 2 LN were extracted, 8mm and 18 mm in diameter. Histological confirmation was obtained for all the extracted lesions. Conclusion: ROLL should be used as an effective technique for minimal invasive parathyroid and thyroid surgery. The ROLL method seems to be very helpful to the surgeons for precise localization of the small lesions. At the same time, shortening the time of the surgical intervention is another significant accomplishment of the technique.
Keywords: roll; radioguided; parathyroid surgery